1,001 Celestial Wonders to See Before You Die The Best Sky Objects for Star Gazers - Bakich, Michael E. (The Patrick Moore Practical Astronomy Series, 2010)
Many deep-sky objects that can appear quite wonderful in photographs can be hard to observe in the telescope. This book is your guide to the more interesting nebulae, star clusters, and galaxies, objects that will bring gasps when you see them through a telescope. Author Michael E. Bakich shows you how to spot constellations you've heard of but haven't been able to find. He gives you lists of bright deep-sky objects to target on clear nights. And he guides your search for the famous named splendors you've heard of - and perhaps seen a picture of - and would like to see through your own telescope. Bakich, an observer since he was in third grade, knows the sky better than most. In his current position as senior editor and also photo editor for the highly regarded Astronomy magazine, he has the technical expertise and finely honed communication skills to help you easily locate the best sites in the sky. His more than 250 astroimages help you identify the detail in these sky wonders. Bakich organizes his 1,001 objects according to their best viewing months, so anytime is a good time to pick up this book and start observing. As long as you know what month it is, just head for that chapter, set up your scope, and off you go!